2021
DOI: 10.1039/d0lc90127j
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Deep-LUMEN assay – human lung epithelial spheroid classification from brightfield images using deep learning

Abstract: Correction for ‘Deep-LUMEN assay – human lung epithelial spheroid classification from brightfield images using deep learning’ by Lyan Abdul et al., Lab Chip, 2020, DOI: 10.1039/d0lc01010c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, benign and malignant nodule classification is a challenge. Many investigators have applied deep learning techniques to help radiologists make more accurate diagnoses [ 12 , 13 , 14 , 15 ]. Previous studies have confirmed that deep learning-based CAD systems can effectively improve the efficiency and accuracy of medical diagnosis, especially for diagnosing various common cancers, such as lung and breast cancers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, benign and malignant nodule classification is a challenge. Many investigators have applied deep learning techniques to help radiologists make more accurate diagnoses [ 12 , 13 , 14 , 15 ]. Previous studies have confirmed that deep learning-based CAD systems can effectively improve the efficiency and accuracy of medical diagnosis, especially for diagnosing various common cancers, such as lung and breast cancers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%